Pengaruh Terapi Benson Terhadap Tingkat Nyeri Dismenore pada Remaja - Kaonang, Mahardika Putri; Jumiati, Silvianingsih; Roufuddin, Roufuddin; Wilujeng, Sri; Widoyanti, Virki; Yobel, Sosilo; Prayoga, Dimas Hadi (Jurnal Medicare, 2025)
Dysmenorrhea is commonly experienced by adolescents and can interfere with daily activities. Benson therapy, a combination of relaxation techniques and repeated affirmations with a regular rhythm accompanied by a surrendering attitude, has been recognized as an effective method for reducing pain in various conditions, including dysmenorrhea. This study aims to determine the effect of Benson therapy on dysmenorrhea pain levels in adolescents in Kampung Tengger Raya, Surabaya. The design used is a one-group pretest-posttest with a sample of 35 female adolescents using a total sampling technique. Data was collected using the Numeric Rating Scale (NRS) to assess pain levels and analyzed using the Paired Sample T-Test. The results showed that before the intervention, the majority of adolescents experienced moderate pain on a scale of 4-6, with the highest level at scale 9. After the therapy, most adolescents reported pain reduction, with the lowest level at scale 2 and the highest at scale 5. The Paired Sample T-Test showed a significant difference, indicating that Benson therapy effectively reduces dysmenorrhea pain levels. This therapy can be applied independently and serves as a useful non-pharmacological alternative for treating dysmenorrhea in adolescents.